Strategies to Achieve Sustainable Development Goals through Diversification of Waqf Products - Amaliah, Ima; Aspiranti, Tasya; Shaharuddin, Amir (KnE Social Sciences, 2024)
Waqf can be used to achieve SDGs. This is evident from the programs rolled out by waqf institutions that have covered several articles in the SDGs, but in fact, they still revolve around the same articles such as no poverty, inequality, health, education, gender, clean water, and sanitation. Therefore, it is important to map the diversification of waqf products so that a waqf diversification strategy can be developed for SDG’s implementation. The method used is descriptive quantitative using data from the annual reports of waqf BSI, Sinergy Foundation, and OJK roadmap. The results of the study show that there are similarities in waqf diversification between waqf institutions where waqf institutions have implemented 6-9 waqf articles (eradicating poverty, ending hunger, good health and well-being, quality education, gender equality, access to clean water and sanitation, clean and affordable energy). Therefore, it is necessary to transform waqf institutions, laws and procedures, digital transformation, and literacy and education. Keywords: diversification strategy, SDG’s, Waqf program